Impact and cause risks of creative accounting in small enterprises: evidence from the Czech Republic - Honkova, Irena (Transformations In Business & Economics, 2026)
Financial statements are a crucial source of information for decision-making, yet their reliability may be undermined by creative accounting, particularly in small enterprises that operate under limited regulation and weak internal controls. This paper examines the extent and causes of creative accounting risks in small enterprises in the Czech Republic, with a focus on discrepancies between earnings before tax and cash flows as indicators of accounting errors and fraud. The analysis is based on a dataset of small enterprises operating in the manufacturing, construction, and trade sectors during the period 2010–2024. Creative accounting risks are identified using the Beneish M-score methodology applied at all three analytical levels. To improve diagnostic precision, the analysis is complemented by six financial indicators and twelve accounting items. Inter-industry differences are assessed using the z-test for equality of proportions. The results reveal that significant earnings–cash flow discrepancies are widespread across all analysed sectors. While impact risks measured by the M-score do not differ substantially between industries, statistically significant differences are observed in cause risks, particularly in profitability-related and accrual-based indicators. Accruals, provisions, and selected revenue and cost items emerge as the most frequent sources of elevated risk, especially in the construction and manufacturing sectors. These findings are consistent with previous evidence for Czech publicly traded companies. The study extends the application of the M-score framework to small enterprises within a European accounting context and provides useful benchmarks for auditors, external users of financial statements, and financial managers aiming to strengthen internal controls and support faithful and fair financial reporting.
Keywords: accounting fraud; financial analysis; cash flows; earnings management